Klasyfikacja pozycyjna : podejście dynamiczne - Strahl, Danuta (Positional Classification : Dynamic Approach, 2008)
The article presents the proposal of classification referring to a set of objects and performed by means of positional statistics in a dynamic perspective. The article focuses on a median and takes into consideration three aspects of a dynamic approach in the procedure for objects classification. 1) performing normalization of attributes value considering the flow of time and applying due formulas for calculating the mean value and standard deviation covering the whole research period, 2) introducing the spatial median into classification procedure in which space is made up of variables values in particular research periods, 3) calculating the value of median for every variable considering its value at each observation point. The article is concluded by an example illustrating the proper procedure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 9-16